2016
DOI: 10.1021/acs.jproteome.6b00369
|View full text |Cite
|
Sign up to set email alerts
|

Combined Antibody/Lectin Enrichment Identifies Extensive Changes in the O-GlcNAc Sub-proteome upon Oxidative Stress

Abstract: O-Linked N-acetyl-β-d-glucosamine (O-GlcNAc) is a dynamic post-translational modification that modifies and regulates over 3000 nuclear, cytoplasmic, and mitochondrial proteins. Upon exposure to stress and injury, cells and tissues increase the O-GlcNAc modification, or O-GlcNAcylation, of numerous proteins promoting the cellular stress response and thus survival. The aim of this study was to identify proteins that are differentially O-GlcNAcylated upon acute oxidative stress (HO) to provide insight into the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 163 publications
1
53
0
Order By: Relevance
“…Second, OGT interacts with p38 mitogen-activated protein kinase during glucose starvation, resulting in the targeting of OGT to glycosylate substrates such as neurofilament H (32). Third, we have recently reported that a subset of proteins exhibit decreased O-GlcNAcylation during oxidative stress, even when global O-GlcNAc levels are elevated (65). To define the regulation of OGA during oxidative stress, we have identified a subset of its interaction partners and determined how these interactions change with oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, OGT interacts with p38 mitogen-activated protein kinase during glucose starvation, resulting in the targeting of OGT to glycosylate substrates such as neurofilament H (32). Third, we have recently reported that a subset of proteins exhibit decreased O-GlcNAcylation during oxidative stress, even when global O-GlcNAc levels are elevated (65). To define the regulation of OGA during oxidative stress, we have identified a subset of its interaction partners and determined how these interactions change with oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…We set an arbitrary threshold of 25% above or below 1.32125 and 0.79275, respectively, for the HA dataset; and 1.635 and 0.981, respectively, for the Myc dataset (supplemental Tables 10 -12). Our rationale for this threshold was as follows: as signal-induced changes are diluted out by the BioID labeling method, we set a lower threshold than we have used previously (30 -50% change (42,65,92)). To validate this threshold, candidate proteins near the threshold (FAS and FLNA) were validated by co-immunoprecipitation.…”
Section: Search Parameters and Acceptance Criteriamentioning
confidence: 99%
“…Several groups, including our own, had observed previously that multiple core COPII proteins are reversibly O-GlcNAcylated, but the biochemical effects of these glycosylation events remained unknown. 6771 Using GlcNDAz, we demonstrated that O-GlcNAc mediates multiple protein–protein interactions of COPII components. We mapped O-GlcNAc sites on several COPII proteins via mass spectrometry and used GlcNDAz and site-directed mutagenesis to pinpoint specific residues on the COPII protein Sec23A that are required for O-GlcNAc-mediated protein–protein interactions.…”
Section: Protein–protein Interactions Induced By O-glcnacmentioning
confidence: 99%
“…It has been shown previously that O -GlcNAc signaling is an essential stress and metabolic sensor, and that global O -GlcNAcylation levels and OGT activity are modulated by various stress stimuli [ 45 ]. Acute oxidative stress can induce both an increase and a decrease in global O -GlcNAcylation, thereby regulating many cellular pathways to promote cell and tissue survival [ 46 ]. Furthermore, enhanced global O -GlcNAc signaling is known to reduce endoplasmic reticulum (ER) stress-induced cell death [ 47 ].…”
Section: Discussionmentioning
confidence: 99%